New perspectives regarding the antiviral effect of vitamin A on norovirus using modulation of gut microbiota. (2nd November 2017) - Lee, Heetae; Ko, GwangPyo
ABSTRACT: Gut microbiota has been revealed to play an important role in various health conditions, and recent studies have suggested the modulation of gut microbiota as a therapeutic strategy. There is no effective treatment of norovirus infection, though vitamin A has been suggested to have an antiviral effect in an epidemiological study. We demonstrated that vitamin A significantly inhibited murine norovirus replication. Vitamin A supplementation significantly increased the abundance of Lactobacillus sp. during norovirus infection, which played a crucial role in antiviral efficacy, inhibiting murine norovirus. Therefore, we elaborated the antiviral effect of vitamin A via modulation of gut microbiota. Furthermore, we suggest a novel strategy, using potential probiotics, as having a protective and therapeutic effect on noroviral infection.